Overview Of Postoperative Nausea and Vomiting (Ponv) in Caesarean Section Patients with Spinal Anesthesia at Fatimah Islam Hospital, Cilacap. - Afrilya, Tiara Octa; Sukmaningtyas, Wilis; Burhan, Asmat (LPPM Universitas Harapan Bangsa, 2023)
Spinal anesthesia has been established as the most effective and safest procedure for Sectio Caesarea. One of the most common side effects of spinal anesthesia is operative Nausea and Vomiting (PONV) or Nausea vomiting, which typically occurs within the first 24 hours after surgery. This study seeks to determine the description of Operative Nausea and Vomiting (PONV) based on age, surgery duration, and fasting duration in patients undergoing Caesarean section at RSI Fatimah Cilacap under spinal anesthesia. This research method employs quantitative analytic observation with a cross-sectional design and convenience sampling. The results revealed that the majority of respondents were between the ages of 20 and 35 (90.6%), with an incidence of PONV of 58.6%; the duration of surgery was between one and two hours (90.6%), with an incidence of 51.7%; and fasting duration was less than six hours (50%) with an incidence of 87.7%. This study found that 53.1% of participants experienced Operative Nausea and Vomiting (PONV).